KEPEMIMPINAN VISIONER KEPALA SEKOLAH DALAM MENGEMBANGKAN BUDAYA ISLAMI DI SDS IT SULTHONIYAH SAMBAS - Bekti Pratiwi; Hifza Hifza; Topik Topik (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Developing Islamic culture in schools means instilling in children good habits that are in line with Islamic values ​​which are manifested in the way students act and behave. The school principal feels it is very necessary to develop these Islamic values ​​and make them a way of life and a guide to behavior. This research was designed using a qualitative approach method and a case study type of research. The data collection techniques are observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data display, and drawing conclusions. The results of this research show that: (1) the visionary leadership competency possessed by the school principal is being able to realize the vision, being a good communicator, having clear leadership targets, being adaptive, and having the effort to provide the best school services, (2) the role of visionary leadership The principal in developing an Islamic culture, namely determining steps and strategies to achieve school goals, anticipating various policy changes, establishing communication and building relationships with internal and external schools, and trying to be a good role model for the school community, (3 ) the implications of the school principal's visionary leadership for Islamic culture, namely the habituation of Islamic values ​​which are based on the school's vision and mission, the creation of an Islamic climate by preparing habituation programs, carrying out regular monitoring and evaluation, and reminding teachers to continue to provide good examples for children and always optimistic in carrying out their roles.